Processing of a LLDPE/HDPE pressure vessel liner by rotomolding - Barboza Neto,E. S. (2014)
Biaxial rotational molding is a low-pressure process that uses a polymer powder to produce large and/or complex-shaped hollow thermoplastic goods using low cost molds, being very suitable for prototype production. In the present work, liner prototypes (F 78 × 280 mm) made of linear low density (LLDPE) and high density polyethylene (HDPE) blends were produced aiming to later use them as compressed natural gas type IV cylinders. The LLDPE/HDPE blend composition and the process parameters (temperature/time cycle, and rotation speed) were varied to evaluate their effect on blend miscibility and liner final properties, such as density and crystallization behavior. Blend composition and process parameters were found vital for the production of a homogeneous wall and for the liner to reach adequate characteristics for the intended product.